Xin-Li-Fang efficacy and safety for patients with chronic heart failure: A study protocol for a randomized, double-blind, and placebo-controlled trial - Liu, Tong; Yao, Sijie; Jiang, Wei; Lan, Taohua; Xu, Wenjing; Cao, Haiming; Yao, Ping; Wang, Chao; Lu, Weihui; Chen, Xiankun (Frontiers in Cardiovascular Medicine, 2023)
Abstract Introduction: Xin-Li-Fang (XLF), as a representative Chinese patent medicine, is derived from the years of clinical experience of academician Chen Keji and is widely used to treat the Chronic Heart Failure (CHF). Previous studies in our team have shown that XLF can improve cardiac function, reduce myocardial fibrosis, and inhibit myocardial remodeling in CHF rats. To further assess the efficacy and safety of XLF in CHF patients, a randomized, double-blind, placebo-parallel controlled preliminary experiment has been conducted by our team, in hope to provide high-quality evidence-based medical evidence for CHF. Methods and design: This study is a randomized, double-blind, placebo-controlled clinical trial applied to evaluate the efficacy and safety of XLF. The Second Affiliated Hospital of Guangzhou University of Traditional Chinese Medicine will recruit 60 CHF patients with qi deficiency, blood stasis and water and dampness retention syndrome, and at the same time, they meet the requirements of cardiac function class II-IV and the content of NT-proBNP in serum ≥ 450pg/ml. These subjects will be randomly divided into Xin-Li- Fang group or placebo group, with 30 patients in each group. Patients in the Xin-Li-Fang group will take 30g XLF per day for 12 weeks, while patients in the placebo group will take XLF placebo for the same duration and dose, and the total follow-up time is 24 weeks. This study will take the proportion of patients whose serum NT-proBNP decreased by more than 30% as the main therapeutic index. The secondary outcomes will include: (1) Minnesota living with heart failure questionnaire; (2) NYHA classification evaluation; (3) 6-minute walking test; (4) TCM symptoms evaluation; (5) the Evaluation Scale of Dampness Syndrome of Traditional Chinese Medicine; (6) primary end point event (including hospitalization for worsening heart failure, all-cause death, other major cardiovascular events, etc.); (7) echocardiography parameters. Discussion: XLF, as an alternative and complementary treatment measure for CHF patients, the safety and efficacy of which will be preliminary assessed in this study. Clinical Trial Registration: Chinese Clinical Trial Registration Center (ChiCTR2200058649). Keywords: Xin-Li-Fang, Traditional Chinese Medicine, Protocol, Chronic Heart Failure, Randomized Controlled Trial